2020
DOI: 10.1177/0018720820969071
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Measurements of Situation Awareness: A Systematic Review

Abstract: Objective The goal of this review is to investigate the relationship between indirect physiological measurements and direct measures of situation awareness (SA). Background Assessments of SA are often performed using techniques designed specifically to directly measure SA, such as SA global assessment technique (SAGAT), situation present assessment method (SPAM), and/or SA rating technique (SART). However, research suggests that physiological sensing methods may also be capable of inferring SA. Method Seven da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 68 publications
0
39
1
Order By: Relevance
“…There is also a difference in gaze patterns depending on the knowledge level of the participant [ 33 , 34 ] as demonstrated in radiology, nursing, and dental education [ 35 , 36 , 37 ]. Cooper et al used eye-tracking technology in radiology where they showed CT-scan slices displaying different pathologies to participants at different levels of medical training.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a difference in gaze patterns depending on the knowledge level of the participant [ 33 , 34 ] as demonstrated in radiology, nursing, and dental education [ 35 , 36 , 37 ]. Cooper et al used eye-tracking technology in radiology where they showed CT-scan slices displaying different pathologies to participants at different levels of medical training.…”
Section: Discussionmentioning
confidence: 99%
“…Although not implemented in this current study, other physiological metrics may also be helpful in monitoring RPA operators. For example, galvanic skin response, muscle activity, pupil diameter, and thermal imaging were other pre-viously used physiological modalities (Charles and Nixon 2019; Wu et al 2021; T. Zhang et al 2021). However, the B-Alert system only had one extra channel (beyond the nine ch an ne ls us ed for E EG), an d w e s e l ec ted ECG f o r measurement.…”
Section: Data Collectionmentioning
confidence: 99%
“…Although work demonstrating the link between phys-iological metrics and constructs such as trust (Akash et al 2018;Dong et al 2015;Fu et al 2018;M. Wang et al 2018) and situation awareness (Catherwood et al 2014;Kaur et al 2019;Yeo et al 2017;Zhang et al 2021) is still developing, the ability of physiological sensors to measure workload has been well-established.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have shown that situation awareness can be inferred through EEG, event-related potential (ERP), heart rate variability (HRB), and skin conduction level (SCL) [31,32]. A recent review on the physiological measures of SA reports the general findings on the studies that investigated the correlations between physiological measures and situation awareness [33]. It was found that eye movements measures and EEG are commonly reported to have correlations with SA.…”
Section: Situation Awarenessmentioning
confidence: 99%